Pengembangan Ekonomi Berbasis Potensi Lokal Untuk Pemberdayaan Pemuda di Desa Binaan Pamekasan (Universitas Hasyim Asy'ari Tebuireng Jombang, 2021)
Community development is the essence of community empowerment, especially in terms of increasing participation in something that will be carried out by a group of people. The fostered village is one of the community development programs with a target location of a village that meets the characteristics to become a fostered village. Developing fostered villages is the right and strategic choice for the benefit of regional development in the current Covid-19 pandemic conditions. One of the developed villages is located in Barurambat Timur Village, Pademawu District, Pamekasan Regency, East Java Province. The method of implementing this community service program is carried out in several stages, including pre-implementation stage, preparation stage, implementation stage and monitoring and evaluation stage. The purpose of this community service activity is to develop the local economy by increasing the capability of youth regarding the processing of products/businesses managed by young people in the target villages. The results that have been achieved in this community service are that by providing socialization and training on the processing of local potential, it can empower youth in the target villages to develop products from the efforts that have been made. This training triggers the youth in the target villages to be creative in creating updates or innovations in processing their local potential. It is hoped that the existence of economic development activities on the local business potential of the youth in the fostered villages can revive the regional economy as a mitigation of the impact of the economic recession due to Covid-19.